2012
DOI: 10.1258/ijsa.2011.011183
|View full text |Cite
|
Sign up to set email alerts
|

A national audit on the management of pelvic inflammatory disease in UK genitourinary medicine clinics

Abstract: The prompt and effective treatment of pelvic inflammatory disease (PID) may reduce the risk of complications such as infertility, ectopic pregnancy and pelvic pain. We conducted a national audit to investigate the treatment of women diagnosed with PID and associated rates of partner notification in genitourinary (GU) medicine clinics during 2008 and compared our results with the British Association of Sexual Health and HIV (BASHH) 2005 national guideline. Among a total of 1,105,587 female attendees, national d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The results revealed that genital tract mycoplasmas were the most encountered micro-organisms (Table 3). 4,6 Our incidence might even been higher than what was found, given that not all women go to hospitals when they are sick. This high rate in our series might be explained by the fact that some women have to depend on their partner(s), given the high rate of underemployment and poverty in our country.…”
Section: Resultsmentioning
confidence: 61%
“…The results revealed that genital tract mycoplasmas were the most encountered micro-organisms (Table 3). 4,6 Our incidence might even been higher than what was found, given that not all women go to hospitals when they are sick. This high rate in our series might be explained by the fact that some women have to depend on their partner(s), given the high rate of underemployment and poverty in our country.…”
Section: Resultsmentioning
confidence: 61%
“…The incidence of acute PID has decreased in many countries, though its true prevalence is not well known because most of cases are subclinical [3,4]. According to previous studies, its incidence varies between 0.28% and 1.67% worldwide [5,6]. PID affects predominately in the reproductive age years with its highest prevalence being in the second and third decades [7].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous sources are sexually transmitted or following induced or unsafe abortion or during delivery in unhygienic surroundings 6 . Risk factors for PID are multiple sexual partners, single status, lower socioeconomic status, young age (<30 years), intra uterine contraceptive device, endometrial biopsy, curettage, hysteroscopy and hysterosalpingography 1,4 .…”
mentioning
confidence: 99%